Comprehensive aerodynamic and dynamic study of independence of ukraine monument - Lebedich, I. M.; Kondra, M. P.; Pavlovsky, R. M.; Vynogradskyy, P. M.; Mostovoy, V. S.; Mostovoy, V. S. (Proceedings of National Aviation University (archive), 2003)
Comprehensive approach for solution the engineering problems o f creation the high-rise extended pillartype Monument in Kiyv is described. The results o f dynamic tests o f 1:25 scale model and aerodynamictests o f 1:8 scale model o f the Monument in TAD-2 wind tunnel are given. The procedures fordetermination o f actual dynamic characteristics and assurance the efficiency o f damping on the siteare described